Telemonitoring: An opportunity in cystic fibrosis lung transplant recipients - Letizia Corinna Morlacchi; Emilia Privitera; Valeria Rossetti; Martina Santambrogio; Angela Bellofiore; Lorenzo Rosso; Alessandro Palleschi; Mario Nosotti; Francesco Blasi (Heliyon, 2023)
Introduction: Telemedicine has been successfully employed in a wide range of conditions, such as such as chronic lung disease and COVID-19. This study evaluate the role of telemonitoring for the early diagnosis of acute lung allograft dysfunction in cystic fibrosis adults who underwent lung transplant (LuTx). Quality of life and functional level achieved during a 12 months follow up were assessed. Methods: Patients were randomized into two groups; control group received traditional hospital-based follow-up, whereas patients in the intervention group received, on top of standard care, a telemonitoring device, with a pulse oximeter and a spirometer integrated. Telemonitoring data were digitally transmitted to our centre. Results: Sixteen patients were enrolled in each group. No statistically significant difference was found between the two groups in terms of incidence of allograft dysfunction, time from onset of symptoms to diagnosis and time of occurrence from LuTx. Moreover, both groups achieved similar quality of life and functional level. With reference to the telemonitoring group: 1) hospital reported data were consistent with those being remotely registered; 2) adherence to telemonitoring decreased during the follow up; 3) the majority of patients reported a high degree of satisfaction. Conclusion: The COVID19 pandemic highlighted the necessity to investigate alternative practices to treat chronically ill individuals. Telemonitoring is a valuable tool to improve quality care to LuTx recipients.